The Internet of Things in Healthcare: A survey for Architecture, Current and Future Applications, Mobile Application, and Security - Ali Mohammad Alqudah (Society of Visual Informatics, 2019)
The internet of things (IoT) are developed toward making the objects smart and connectable using recent development in miniaturizing and communication technologies, IoT has wide application domains one of them is healthcare. this paper focusing on the IoT and their applications, integration, and advances in use in the healthcare sector. IoT is promising technology which will provide an advancement in healthcare providing techniques especially in telemetry and home care. Moreover, IoT will provide a framework for health data collection and sharing. This paper will discuss recent developments in applications and innovation of using IoT in healthcare such as miniaturizing technology and wearable technology as well as the changes facing the application of IoT in healthcare.